(untitled) - Koyama, Denzo K. (Tokyo, 1935)
Book contains important foreign business methods of Japanese
Keywords: Foreign trade regulation,Quy tắc ngoại thương,Thương mại quốc tế,International trade,Thương mại Nhật Bản,Japan; Commerce